Modeling and transient stability analyzing of type 1 speed governor model (IEEEG1) using dynamic computation for power system (DCPS) / Che Kamariza Che Ismail - Che Ismail, Che Kamariza (2009)
The objective of this thesis project is to investigate and understand the stability concept of power system, with the main focus on stability theories and power system modeling. The thesis looked into the effects that advanced control techniques have on electrical power generation system and transmission system. The thesis first explained the definition of power system stability and the need for power system stability studies. It then proceeded to discuss on the various stability problems after which the thesis provided a brief introduction on basic control theory and study. The thesis presents the modeling of type 1 speed governor model (IEEEG1) and transient stability analysis. The dynamic computation for power system (DCPS) software modeling was used in the system. The simulation is done for the six test bus system and the study involved electrical power, rotor angle, voltage magnitude and speed of the machine. In simulation, the Euler method was used to linearized each block diagram and modified the block diagram of the IEEEG1 model. The thesis also present the comparison of critical clearing time at bus 100, bus 200, bus 300, bus 400, bus 500 and bus 600 after faults was occurred in the system.